Sand filters for removal of microbes and nutrients from wastewater during a one-year pilot study in a cold temperate climate - Kauppinen, Ari; Martikainen, Kati; Matikka, Ville; Veijalainen, Anna-Maria; Pitkänen, Tarja; Heinonen-Tanski, Helvi; Miettinen, Ilkka T. (Journal of environmental management, 2014)
Onsite wastewater treatment systems (OWTS) are recognised as potential threats to groundwater or other water environments subject to discharged effluents. In this study, the microbiological and nutrient removal properties of three different pilot-scale sand filters (SFs) were followed over a one-year period. Moreover, a separate phosphorus removal unit was tested for six months. For the best treatment system, the average log removals were 2.2–3.5 for pathogenic human noro- and adenoviruses and 4.3–5.2 and 4.6–5.4 for indicator viruses and bacteria, respectively. The system that effectively removed microbes was also efficient at removing nutrients. However, the poorest treatment system yielded substantially lower removals. The remarkable differences noted between the studied SFs highlights the importance of construction materials and the careful planning of the filters. Moreover, seasonal conditions appear to have a clear effect on purification efficiencies, emphasising the vulnerability of these systems especially in cold climates. •Sand filters (SFs) showed high variation in performance.•An SF with a layer of biotite was the most effective system.•Especially the removal of viruses tends to decrease during a cold period.•Only limited correlations were noted between the removal of different microbes.•Pathogenic microbes may penetrate the SFs causing risks to water environments.